2020
DOI: 10.47881/168.967x
|View full text |Cite
|
Sign up to set email alerts
|

Rainfall Distribution in the Upper East Region of Ghana, 1976 – 2016

Abstract: The knowledge and understanding of rainfall distribution of a region are very essential and useful in determining the overall impacts of climate change, especially to the agricultural sector. Monthly rainfall data from 1976-2016 for five selected stations were acquired and subjected to various statistical techniques namely coefficient of variation, 5-year moving average and departure from the mean to obtain the variability and trends in the data. The results showed that the selected stations have uni-modal rai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 11 publications
3
2
0
Order By: Relevance
“…An appraisal of available mean annual rainfall data from the Ghana Meteorological Agency for the Zuarungu weather station from 1980-2011, and analysis on rainfall departure from the mean between 1976-2016 [78], corroborate the observations of people and findings regarding the rainfall pattern in the study area. From Figure 2, the data depicts fluctuations in precipitation which mark alternating periods of wet and dry hydrological years in the area.…”
Section: Climate Change and Drought Perceptions Amongst Local Farmerssupporting
confidence: 69%
See 1 more Smart Citation
“…An appraisal of available mean annual rainfall data from the Ghana Meteorological Agency for the Zuarungu weather station from 1980-2011, and analysis on rainfall departure from the mean between 1976-2016 [78], corroborate the observations of people and findings regarding the rainfall pattern in the study area. From Figure 2, the data depicts fluctuations in precipitation which mark alternating periods of wet and dry hydrological years in the area.…”
Section: Climate Change and Drought Perceptions Amongst Local Farmerssupporting
confidence: 69%
“…In relating these observations to similar findings on the nature of rainfall activity and distribution, specifically for Upper East Region (1976-2016), Ampadu et al [78] (p. 54) have also alluded to high annual variability and prolonged inter-seasonal dry spells for all the stations considered. Besides their observation of the hydrological years of 2013-2015 as the most recent worst dry period with significant departures from the annual mean, they also found that there had generally been a decline in the distribution of rainfall in the study area and entire country over the last four decades [78,79]. The rainfall departures from the annual mean and negative trend recorded in the study region are indicative of drought events during the period.…”
Section: Climate Change and Drought Perceptions Amongst Local Farmerssupporting
confidence: 63%
“…This trend, they attributed to such anthropogenic activities as deforestation, poor farming practices, overgrazing, harvesting wood for energy, and bushfires. Some other studies (e.g., Ampadu, 2008;Ampadu et al, 2019) were localized and mostly came up with similar conclusions on rainfall, even though some showed some increasing trends. Asante and Amuakwa-Mensah (2015) also projected low rainfall occurrence in 2020, 2050, and 2080, corroborating similar studies.…”
Section: Climate Change and Rainfall Evapotranspiration And Rh Dynamicssupporting
confidence: 55%
“…Rainfall follows a unimodal pattern [31], with an average annual rainfall of 921mm, ranging from 645mm to 1250mm, creating a growing season lasting approximately 5 to 6 months from April/May to September/October, followed by a long dry and hot season lasting 6 to 7 months from October to April. The annual average temperature ranges from a minimum of 15°C during the dry season (December to February) to a maximum of 45°C in March and April [30].…”
Section: Description Of Study Area and Data Sourcementioning
confidence: 99%